2017
DOI: 10.1155/2017/9401606
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Exenatide and Metformin Monotherapy in Overweight/Obese Patients with Newly Diagnosed Type 2 Diabetes

Abstract: Aims The present study assessed the therapeutic effect of exenatide and metformin as the initial therapy on overweight/obese patients with newly diagnosed type 2 diabetes (T2D). Methods The prospective, nonrandomized, interventional study enrolled a total of 230 overweight or obese patients with newly diagnosed T2D who were administrated exenatide or metformin hydrochloride for 12 weeks. Results 224/230 patients, including 106 in the exenatide group and 118 in the metformin group, completed the 12-week treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Importantly, these alternative strategies also lead to modest but significant body weight reductions. 36,37 Preventing access to CNS GLP-1Rs is the probable explanation for the lack of B12-Ex4-induced emesis in the shrew. Our immunohistological evidence supports this notion as we observed sparse c-Fos activation following systemic B12-Ex4 administration in the AP and NTS, two hindbrain nuclei known to mediate feeding behaviour and emesis, 13,[38][39][40][41] while native Ex4 produced robust activation of these nuclei.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, these alternative strategies also lead to modest but significant body weight reductions. 36,37 Preventing access to CNS GLP-1Rs is the probable explanation for the lack of B12-Ex4-induced emesis in the shrew. Our immunohistological evidence supports this notion as we observed sparse c-Fos activation following systemic B12-Ex4 administration in the AP and NTS, two hindbrain nuclei known to mediate feeding behaviour and emesis, 13,[38][39][40][41] while native Ex4 produced robust activation of these nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…dipeptidyl peptidase‐4 inhibitors, metformin and sodium‐glucose co‐transporter‐2 inhibitors) do not achieve the same overall positive outcome on glucose handling compared with GLP‐1R agonists. Importantly, these alternative strategies also lead to modest but significant body weight reductions 36,37 …”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were collected after overnight fasting and stored at −80°C until lipidomics analysis. The general methodology for clinical measurements is described in our previous study ( 16 , 20 ). Eligible T2DM subjects received a continual subcutaneous injection of exenatide for a total of 12 weeks (5 µg twice a day for 4 weeks, followed by 10 µg twice a day for 8 weeks).…”
Section: Methodsmentioning
confidence: 99%
“…22,23 As MH increases glucose utilization in muscle and adipose tissue while inhibiting glucose absorption in the intestinal tract, its application in the treatment of diabetes usually leads to an increase in body weight loss. 24 In contrast, after a 4-week treatment, both DAGL and DAGL·Cr significantly increased the body weight of T2DM mice, possibly because DAGL and DAGL·Cr promote glucose absorption and reduce energy loss. 25 Notably, the results revealed that DAGL·Cr had a better effect on the restoration of body weight than DAGL, suggesting that the complexation of Cr( iii ) improved the weight loss of T2DM mice; similar results were also reported by Yanni et al .…”
Section: Discussionmentioning
confidence: 90%
“…tinal tract, its application in the treatment of diabetes usually leads to an increase in body weight loss. 24 In contrast, after a 4-week treatment, both DAGL and DAGL•Cr significantly increased the body weight of T2DM mice, possibly because DAGL and DAGL•Cr promote glucose absorption and reduce energy loss. 25 Notably, the results revealed that DAGL•Cr had a…”
Section: Food and Function Papermentioning
confidence: 91%